2016
DOI: 10.1021/acs.jctc.6b00314
|View full text |Cite
|
Sign up to set email alerts
|

Conformers of Gaseous Serine

Abstract: The myriad conformers of the neutral form of natural amino acid serine (Ser) have been investigated by systematic computations with reliable electronic wave function methods. A total of 85 unique conformers were located using the MP2/cc-pVTZ level of theory. The 12 lowest-energy conformers of serine fall within a 8 kJ mol(-1) window, and for these species, geometric structures, precise relative energies, equilibrium and vibrationally averaged rotational constants, anharmonic vibrational frequencies, infrared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 110 publications
(265 reference statements)
5
48
0
Order By: Relevance
“…5d) in the water phase using the integral equation formalism variant (IEFPCM). 50 It was known that both cis-COOH and trans-COOH belong to the ensemble of possible conformations, 59 but analysis of the energies revealed that the ciscarboxyl was intrinsically more favourable than the transcarboxyl by approximately 3.1 kcal mol À1 , with a barrier of 10.9 kcal mol À1 (Fig. 5d).…”
Section: Interactions Between the Surfactants And Liquid Water Bridgementioning
confidence: 99%
“…5d) in the water phase using the integral equation formalism variant (IEFPCM). 50 It was known that both cis-COOH and trans-COOH belong to the ensemble of possible conformations, 59 but analysis of the energies revealed that the ciscarboxyl was intrinsically more favourable than the transcarboxyl by approximately 3.1 kcal mol À1 , with a barrier of 10.9 kcal mol À1 (Fig. 5d).…”
Section: Interactions Between the Surfactants And Liquid Water Bridgementioning
confidence: 99%
“…In the present study, we have selected the four lowest energy serine conformers labeled as I, II, III and IV ( Figure 1) out of 85 conformers reported in literature. 1 Conformer I possess a trans-COOH, allowing a strong intra-molecular HB (N • • • H-O) to be formed between the hydroxyl (O-H) group of the carboxylic moiety and non-bonding electron pair at the nitrogen atom. Also, a weaker intra-molecular HB (N-H • • • O) is established between one of the amino H atoms and the 'O' atom of the side chain -CH 2 OH.…”
Section: Conformational Stabilitymentioning
confidence: 99%
“…It is a component of brain proteins, nerve sheaths and is important in the formation of cell membranes. Over the past few years, the conformational behaviour of serine has been the subject of many theoretical [1][2][3][4][5][6][7][8][9][10][11] as well as experimental studies. [5][6][7][8][9][10][11] The hydrogen bond (HB) is an extremely important molecular interaction as it is inherently present in many biological systems and plays a crucial role in a number of biochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, CREST generated 90 conformers for serine for which 85 were found in ref. 1 while CONFAB did not identify the correct rotatable bonds and afforded only 36 conformers. Figure S3.…”
Section: Limitationsmentioning
confidence: 99%
“…Automating the search for new chemical reactions is seen as one of the 'grand challenges' in computational chemistry. 1,2 Discovering such thermodynamically and kinetically accessible reactions requires knowledge of the underlying potential energy surface (PES), which to a first approximation, involves the characterization of reactants, products, intermediates, and transition states (TSs). [3][4][5] While this has been routine for computational chemists for decades, locating TSs remains time consuming and a highly non-systematic endeavour.…”
Section: Introductionmentioning
confidence: 99%